Application of Method of Financial Risk in Serbian Companies - Survey Sample Company - Bulatovic, Jelisavka (International Journal of Economics and Financial Issues, 2011)
The aim was to obtain information on the use of financial instruments hedging the Serbian large and medium-sized enterprises, as well as to detect any differences between the characteristics of companies that use them or not used. Survey researches based on telephone interviews with financial or accounting managers with a stratified random sample of 101 Serbian companies and conducted in 2010. The contribution of this study comes from testing hypotheses about the relationships between the characteristics of Serbian companies and the use of financial instruments hedging. Finally, in the future, researchers should make use of this work and make a deeper study based on differentiation from Serbian companies. In this way, it would be possible to include different sizes of companies (on the number of employees) to include different types of financial measures in relation to the size of the company, for example, the factor of annual revenues. Keywords: Financial risk management instruments, Survey research, χ2-test of independence, t-test differences of means